New strategy for rare sugars biosynthesis: Aldol reactions using dihydroxyacetone phosphate (DHAP)-dependent aldolases. (December 2021) - Dai, Yiwei; Zhang, Jinxiu; Jiang, Bo; Zhang, Tao; Chen, Jingjing
Abstract: Rare sugars have various biological functions but they exist in low amounts in nature. Enzymatic synthesis of rare sugars is typically synthesized via single-enzyme catalysis based on the Izumoring strategy. However, some transformations such as C-4 epimerization could not be directly realized through this strategy, and they may suffer from the scarcity and high cost of substrates. Therefore, novel pathways have been developed as complementary methods for efficient synthesis of rare sugars. Aldolases, which commonly catalyzed the aldol reactions in chemical industries, have been recently used in rare sugars synthesis. Among them, dihydroxyacetone phosphate (DHAP)-dependent aldolases have been widely applied in multi-enzyme catalytic pathways, both in vivo and in vitro . They catalyze the reactions of DHAP and a variety of aldehydes. The pathways involving DHAP-dependent aldolases and phosphatases can be used to produce rare sugars and their derivatives. This review presents a detailed discussion on the metabolic roles and enzymatic properties of DHAP-dependent aldolases. Progresses in the engineering of DHAP-dependent aldolases such as genetic modifications, immobilization, and novel enzymes discovery, are described. Furthermore, the types of rare sugars that could be synthesized using DHAP-dependent aldolases are summarized. Current limitations and areas for improvement in the application of DHAP-dependent aldolases are also highlighted.